The Participatory Resilience of Waste Pickers at the Bantargebang Waste Processing Site after Land Degradation - Titisia, Denti; Wicaksani, Dinie Wulan; Rif’an, Fadil Ainur (PCD Journal, 2023)
This study discusses the participatory resilience of the waste pickers at the Bantargebang Waste Processing Site by analysing the link between the waste pickers’ resilience and public participation after land degradation occurs. Similar studies use qualitative evidence to understand how public participation is driven by the issue of land degradation. However, this approach also begs the question as to the roles of the actors and publics involved. This study thus divides actors into two categories, i.e., implementing actors and capital-holding actors. More specifically, this study seeks to understand the realisation and practice of participatory resilience in Bantargebang. For data collection, three methods were used: library research, interviews, and observations.